CONSUMPTION OF DRY GEOTHERMAL ENERGY - Salobir, Boris (Journal of Energy Technology, 2024)
Geo thermal energy is a very high efficiency alternativeresourceofusing the warm in genergy of the Earth. But infact, only 0.1% of today’s world energy is made from the alternative resources. Slovenia has alarge potential for the exploitatio no flow enthalpy geot her malresources. Low enthalpy geothermal resources are exploited for direct use (balneology, agriculture, aquaculture, industrial use ands paceheating). Potential investors are encouraged to consider geothermal energy use owingto the oscillationof fossil fuel pricesandalso due to the creation of extravalue with non energetic water use. Geological research providesbasic information needed for the estimation of exploitabl eenergy resources preserved in the Earth’sinterior. This in formation must answer the questions related to the conditions of geothermal resources’ appearance (existence, spatial extension, temperature) and to the conditions of intake and use of geothermal resources in connection with technological requirements (exploitability, capacity, ecological point of view, maintenance,...). Since the mechanis mand geometry of geothermal systems are mostly not completely solved, or are not solved at all, this applied research project intends to develop improved conceptual models of more interestinggeo thermalresources, using recent results of structural and regional geology. In this way the improved models will serve for the forecastofrechargeanddis charge mechanisms of thermal aquifer, longͲterm influence of exploitation of underground water and/orfortheselectionoflocations with potential for geothermal resource existence.